Gimme shelter : misadventures and misinformation - Cronin, Doreen (Cronin, Doreen. Chicken Squad., 2017)
The Chicken Squad uncovers mysterious remains while digging a meteor/storm shelter, and they stop work to investigate just as a big storm is approaching.